ANALISIS KELAYAKAN PROYEK INVESTASI PENINGKATAN KAPASITAS TERPASANG PADA ASPEK FINANSIAL MELALUI PENDEKATAN SIMULASI (STUDI KASUS : PLTU MUARA KARANG #123) - Hidayat, Rachmat
Abstrak : Based on three forecast scenarios of electricity growth demand in the Java- Bali interconnection system, there will be seriously power supply shortage in Jakarta and the nearby areas occur in 2003 (optimistic growth), 2004 (moderate growth) and 2005 (pessimistic growth). Anticipating the shortage, PT PJB, as power producer in Indonesia, plans to make investment to increase the installed capacity of its plants. This mainly focused in supporting the power supply for Jakarta area . The investment shall be Repowering or Developing New Plant. Repowering shall be done for Muara Karang Steam Power Plant # 123. Considering the company policy on increasing thermal efficiency, minimizing environment effects and continuing natural gas supply as primary energy, then the investment shall be Combined Cycle Power Plant technology-based. Feasibility study of an investment financially depends on rate of return. As for the long term investment may occur changes in any situation, the size of rate of returns gained in the future may contain uncertainty and will raise rate of return variability. This criteria decision is based on Internal Rate of Return achievement probability, deviation standard, and variety of coefficient. Simulation method shall be applied to analyse the IRR achievement probability. The investment is considered to be feasible if the average of IRR resulted in the simulation is higher than the minimum interest rate required (hurdle rate). This study has identified factors which will raise the risk of investment shown through CF (Capacity Factor), sales price, and Rupiah vs. US$ exchange rate. Increasing number of random, simulation process on Repowering, as investment alternative, will produce random variety and result in IRR value on minimum Equity with the sum of minimum 15,27%, maximum 27,96% and average. 21,55%, standard deviation 2,54% and variety coefficient 0,118 with achievement probability to gain IRR higher than minimum Equity 94,87% for the Repowering. While Developing New Plant as another investment alternative describes IRR values on minimum Equity 12,07%, maximum 22,04%, average 17,33%, standard deviation 2,10% and variety coefficient 0,121 with achievement probability to gain IRR higher than minimum Equity 99,46%. The two analysis above explain the reason to choose Repowering as the more valuable investment in overcoming the shortage. However, Repowering shall bring non-feasible performance with probability 5,13%. Therefore, for further decision, PLN needs to review the transmission system planning 1501500kV Area-I to support Repowering investment planning.